Tum/RacGAP functions as a switch activating the Pav/kinesin-6 motor - Li Tao (Nature Portfolio, 2016)
Centralspindlin consists of dimeric kinesin-6 and dimeric RacGAP, and is involved in the organization of anaphase midzone microtubules. Here, the authors show that the RacGAP is needed for motor activity at the plus-end of microtubules, but not for the bundling activity associated with kinesin-6.